The third dose of measles-containing vaccine induces robust immune responses against measles in young seronegative healthcare workers who had previous two-dose measles vaccination - Yong Chan Kim; Heejin Nam; Jun Yong Choi; Eui-Cheol Shin; Young Hwa Choi (Journal of Infection and Public Health, 2023)
Background: Despite the low measles antibody positivity rate among young healthcare workers (HCWs) who have previously received two doses of a measles-containing vaccine (MCV), whether an additional dose of MCV acts as a booster remains unknown. Thus, we aimed to evaluate the immune responses to a third dose of MCV in young HCWs. Methods: Hospital-wide measles seroprevalence was assessed using enzyme-linked immunosorbent assay (ELISA). The immunogenicity of a third dose of MCV was determined in young seronegative HCWs (born between 1986 and 1997) who had previously received a two-dose measles vaccination. Results: A total of 3033 (92.6%) HCWs had anti-measles immunoglobulin G. The lowest seropositivity rate was observed in HCWs aged 20–24 years (87.7%). In this group, HCWs who received a third dose of MCV had higher seropositivity than those who received a second dose (89.5% vs. 75.4%). A third dose of MCV was administered to 18 HCWs who did not have anti-measles IgG despite two doses. Neutralizing antibody titers increased significantly 4 weeks after the third vaccination. Although neutralizing antibody titers decreased 1 year post vaccination, 17 (94.4%) HCWs had medium (121–900 mIU/mL) or high (>900 mIU/mL) levels. Furthermore, the third dose of MCV increased the measles virus-specific T-cell effector function. Conclusions: The third dose of MCV induced a strong immune response against measles in young seronegative HCWs who had previously received a two-dose measles vaccination.